Konversi Gas CO2 menjadi Gas Metana (CH4) menggunakan Katalis Ni/Al2O3 - Saputra, Mailanda; Amin, Jaksen M; Junaidi, Robert (Universitas Pahlawan Tuanku Tambusai, 2024)
Carbon dioxide (CO2) pollution is a global environmental issue that needs to be addressed. Data from the Indonesian Central Statistics Agency shows that CO2 emissions in Indonesia increased by 4.54% from 2015 to 2019. One of the researched solutions is the conversion of CO2 into methane gas (CH4) through the methanation process. This study uses a Nickel (Ni) catalyst with Al2O3 support to investigate the effect of temperature and catalyst mass variations on the conversion of CO2 into CH4. The aim of this research is to study the impact of variations in Ni/Al2O3 catalyst mass and production temperature on the conversion of CO2 into CH4 gas. Ni catalyst was chosen for its ability to absorb hydrogen and its high selectivity in CH4 formation. The use of a stainless steel reactor with a heating coil allows for higher operating temperatures compared to previous studies using glass reactors. The results of the study show that the higher the mass of the Ni/Al2O3 catalyst (5 g, 10 g, 15 g) and production temperature (100°C, 120°C, 150°C), the higher the percentage of CO2 conversion into CH4. The highest CH4 conversion percentage was obtained using 15 g of Ni/Al2O3 catalyst and a production temperature of 150°C, reaching 25.27%. This indicates that the quality of the CH4 gas produced is significantly influenced by the catalyst mass and production temperature. Additionally, the remaining unreacted CO2 gas also decreases with increasing catalyst mass and production temperature.